2019
DOI: 10.3139/120.111330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water absorption on the flexural strength of a green sandwich composite

Abstract: The main objective of this paper is to study the effect of water absorption on the flexural strength of new green sandwich composite material made of flax as skin reinforcement and agglomerated cork as core. In this work, three different types of skin reinforcements and three different densities of agglomerated cork core have been used for the manufacturing of sandwich composites. The manufactured sandwich composites were subjected to three-point bending tests under both dry and wet conditions. The three-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The authors have already developed an NSP made of flax and agglomerated cork and tested its flexural strength, and the results showed that NSP has a higher specific flexural strength. 20 The secondary performance criteria such as thermal insulation, vibration damping, and sound absorption properties were also found to be good for the NSP. 5,21 In continuation with the work and to understand the mechanical behavior of sandwich panels, flatwise tensile tests, flatwise compressive tests, and edgewise compressive tests were carried out.…”
Section: Introductionmentioning
confidence: 88%
“…The authors have already developed an NSP made of flax and agglomerated cork and tested its flexural strength, and the results showed that NSP has a higher specific flexural strength. 20 The secondary performance criteria such as thermal insulation, vibration damping, and sound absorption properties were also found to be good for the NSP. 5,21 In continuation with the work and to understand the mechanical behavior of sandwich panels, flatwise tensile tests, flatwise compressive tests, and edgewise compressive tests were carried out.…”
Section: Introductionmentioning
confidence: 88%
“…[34][35][36] The concept of the sandwichcomposite was developed to reproduce the advantages of the I beam which serves as an efficient-structure since the maximum volume of material is placed on the flanges farthest away from the neutral axis. [37] This design helps in achieving greater material efficiency. A composite sandwich consists of three layers, the top and bottom layers consist of a thin material called skin.…”
Section: Introductionmentioning
confidence: 99%
“…The result portrays that eco-friendly sandwich has good sound absorption capability due to the tortuous passage of fiber and natural honeycomb structure of the core. 1 The authors have developed a novel green composite sandwich made of flax fiber as skin reinforcement and agglomerated cork as core and tested for their mechanical properties and the results were published 20 The secondary performance criteria like vibration damping, sound absorption, thermal conductivity and flame retardant properties were also found to be good for green composite sandwich. 21,22 In continuation with the work, the present study focuses on assessing the biodegradability of a green composite sandwich made of flax fiber as skin reinforcement and agglomerated cork as core material in a natural soil burial environment and verified with morphological, spectrum and thermoanalytical tests.…”
Section: Introductionmentioning
confidence: 99%